Evaluating the historical sedimentation patterns in two different Mediterranean deep environments (Sardinia and Sicily Channels) - HASSEN, NOUR EL HOUDA; REGUIGUI, NAFAÂ; HELALI, MOHAMED AMINE; MEJJAD, NEZHA; LAISSAOUI, ABDELMOURHIT; BENKDAD, AZZOUZ; BENMASOUR, MONCEF (Mediterranean Marine Science, 2019)
The sediment accumulation rate in the Sardinia and Sicily channels in the central part of the Mediterranean Sea was studied by using short-lived radionuclides (210Pb and 137Cs) in two deep sediment cores. Different sedimentation regimes were identified indicating substantial differences in accumulation rates and historical patterns. The 210Pb-derived mean accumulation rate found in the Strait of Sardinia was 0.05 g.cm-2.y-1, lower than that in Sicily Channel (0.1 g.cm-2.y-1) suggesting an inverse correlation with water depth. Excess 210Pb inventories were 24 ± 1 and 6.0 ± 0.4 kBq.m-2, while the fluxes to the sediment were 745 ± 31 and 188 ± 11 Bq.m-2.y-1 in Sicily and Sardinia channels, respectively. 137Cs failed to use for the validation of the established chronologies, while its inventories found 450 Bq.m-2 and 355 Bq.m-2 in the Sicily and Sardinia channel, respectively.